The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1109/tps.2007.892718
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cosmic Dust Bunnies

Abstract: Abstract-Planetary formation is an efficient process now thought to take place on a relatively short astronomical time scale. Recent observations have shown that the dust surrounding a protostar emits more efficiently at longer wavelengths as the protoplanetary disk evolves, suggesting that the dust particles are coagulating into fluffy aggregates, "much as dust bunnies form under a bed."One poorly understood problem in this coagulation process is the manner in which micron-sized, charged grains form the fract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The electrostatic charge and dipole moment of individual particles in a cloud of spherical dielectric particles, dispersed in air passing through a non-uniform electric field, has been experimentally measured in [31] by studying the particles' trajectories. In numerical studies, the electric charge and dipole moment of aggregates in a plasma environment has been calculated using modified OM L theory [32] and the interaction between two charged grains modeled by calculating the torques and accelerations due to the charged aggregates or external electric fields [23,33]. However a direct study of both electrostatic charge and dipole of dust particles in laboratory plasmas has not yet been made.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic charge and dipole moment of individual particles in a cloud of spherical dielectric particles, dispersed in air passing through a non-uniform electric field, has been experimentally measured in [31] by studying the particles' trajectories. In numerical studies, the electric charge and dipole moment of aggregates in a plasma environment has been calculated using modified OM L theory [32] and the interaction between two charged grains modeled by calculating the torques and accelerations due to the charged aggregates or external electric fields [23,33]. However a direct study of both electrostatic charge and dipole of dust particles in laboratory plasmas has not yet been made.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, aggregates were created by numerically modeling the interactions between colliding particle pairs [11]. Working in the center of mass (COM) frame of an initial seed particle, a second monomer or aggregate was chosen to approach this particle from a random direction.…”
Section: Methodsmentioning
confidence: 99%
“…The charge on an aggregate is approximated using both the monopole and dipole moments [11], while the magnetic dipole moment is calculated as the vector sum of the dipole moments of the individual monomers. …”
Section: Methodsmentioning
confidence: 99%
“…Charging effects are usually considered to be insignificant, or are merely mentioned as an after-thought (Blum & Wurm 2008). Recently, simulations have shown that the effect of even a very modest grain charge can not be neglected; as such, a self-consistent charging/coagulation approach for plasma environments relevant to PPDs seems to now be in order (Matthews et al 2007;Okuzumi 2009). Recent experiments have also provided evidence for run-away growth induced by electrostatic dipole interactions, showing that charging of particles can in fact speed up the coagulation processes (Konopka et al 2005), as was also shown numerically (Matthews & Hyde 2009).…”
Section: The Formation Of Planetsmentioning
confidence: 99%
“…The code has since been modified and extended to include the effects of charged particles and magnetic fields (Matthews & Hyde 2003;Vasut & Hyde 2001;Qiao et al 2007). The modified code treats accelerations caused by interactions of charged grains as well as rotations induced by torques due to the charge dipole moments (Matthews et al 2007). These dipole-dipole interactions have been shown to greatly enhance the collision rate, even for like-charged particles (Matthews & Hyde 2009).…”
Section: Aggregate Buildermentioning
confidence: 99%